The teaching process of mixed research methods in the Tourism Research subject: a case study of the Autonomous University of Ciudad Juárez, Mexico - González Herrera, Manuel Ramón (Edward Elgar Publishing, United Kingdom, 2024)
Scientific and research education is a fundamental area for university tourism education since it contributes to scientific tourism thought, based on which the appropriation of scientific methods that allow tourism study is required. In this sense, it is necessary to promote the training of new professionals with a thought that supports the implementation of mixed research methods to generate new integrated tourism knowledge. This chapter aims to systematize the teaching process of mixed research methods and infer the main learning lessons derived from teaching practice based on the development of the Tourism Research subject for more than ten years at the Autonomous University of Ciudad Juárez. It is empirical and theoretical research in which mixed data sources were used. The theoretical scope was based on the literature review as the basis for understanding mixed methods utilizing the author`s triangulation. The applied case study was developed with students of the advanced level of the degree in tourism who studied Tourism Research I and II subjects. As a result, the analysis of the reflective academic practice of teaching mixed research methods in the Tourism Research subject and the main implemented strategies are presented.